INVESTIGATING THE LOW-INCOME SETTLEMENT IN AN URBANIZATION AND URBAN FORM A CONSEQUENCES OF BANGKOK GROWING CITY, THAILAND - U. Shummadtayar; K. Hokao; P. Iamtrakul (Lowland Technology International, 2013)
A rapid urbanization has resulted in more rush transformation of a settlement of low-income migration growth into an urban area. The growt squatter settlement role was influenced through an urban form conflict. Many of these points have been debated over the issue of sustainable urban development plan that has led the way into the urban building density appearance and the phenomenon of its urban area growth effects. The ultimate results depend on an increase in carbon emissions changed over time and its effect on climate change. The real challenged problems are being solved in the developing country, such as Thailand's capital Bangkok. Moreover, an unplanned and low-efficient development projects cause extensive devastating consequences to both urban environment and human beings. Particularly for the low-income people who live in a lowland area are more heavily buderned by environmental risks and unsafe area. Thus, it is imperative for this paper to discover a key issue of low-income migration and settlement on the basis of the measurements which includes: (a) the situation of urbanization driving process forces the low-income settlement growth, and (b) investigate the causes and effects on urbanization in terms of the urban environmental conditions and locations system (e.g. sensitivity analysis, risk approaches) using GIS-based Multi-Criteria Decision Analysis (MCA) for calculating the simplify situations of the alternative factors and using the Analytical Hierarchy Process (AHP) for weighting the measure of individual participant data. By this approach, it is becoming more feasible to be configured, with the Weighted Linear Combination (WLC) operators. This tool presents the usefulness of the relative important weights for relevant approaches of low-income settlement in consequences of growing cities based on geographic information system (GIS).